How do English for Nusantara textbooks represent identity and politeness to develop students’ sociolinguistic competence? - Farida Indri Wijayanti; Fitri Ana Ika Dewi; Linda Safitri; Fatimah Fatimah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study examined how the English for Nusantara textbooks represent identity and politeness in fostering students’ sociolinguistic competence across multiple grade levels. Using a qualitative case study design with content analysis, the study analyzed 93 identity-related words and phrases from all texts and 208 politeness-related utterances drawn exclusively from scripted dialogues. The findings indicate that the textbooks promote national identity through the incorporation of local names, places, foods, address forms, and other cultural references into English discourse. In terms of politeness, the textbooks contain 19 bald-on-record, 170 positive politeness, 18 negative politeness, and 1 off-record strategy, with positive politeness emerging as the dominant strategy that fosters solidarity, approval, and cooperation in peer interactions. Overall, the findings demonstrate that the English for Nusantara textbooks represent learners’ sociolinguistic competence through language identity and politeness. However, this representation remains partial and requires further development to more comprehensively capture uniquely Indonesian identities and a broader range of politeness strategies. This highlights the need for more comprehensive cultural content and more varied interactional contexts, encompassing both formal and informal interactions that reflect authentic language use.